2010
DOI: 10.3390/s100505031
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Glucose Sensors in Pancreatic β-Cells and Liver: An Update

Abstract: Pancreatic β-cells and the liver play a key role in glucose homeostasis. After a meal or in a state of hyperglycemia, glucose is transported into the β-cells or hepatocytes where it is metabolized. In the β-cells, glucose is metabolized to increase the ATP:ADP ratio, resulting in the secretion of insulin stored in the vesicle. In the hepatocytes, glucose is metabolized to CO2, fatty acids or stored as glycogen. In these cells, solute carrier family 2 (SLC2A2) and glucokinase play a key role in sensing and upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 136 publications
(148 reference statements)
1
25
0
Order By: Relevance
“…It has been reported that TCH had no effect on the insulin content of islets [2]; low serum insulin in our study may be therefore due to changes in insulin secretion. Data show that low insulin increases GLUT2 mRNA expression in liver [77] ; in addition, liver GLUT2 expression in diabetic rats is higher, findings supporting the idea that hyperglycemia has a positive role in expression of GLUT2 [78]. To sum up, our findings showed that thyroid hormone deficiency during fetal life impairs glucose sensing apparatus in pancreatic islets and liver of offspring rats during adulthood, changes which may all be involved in impaired insulin sensitivity observed in our study.…”
Section: Discussionsupporting
confidence: 76%
“…It has been reported that TCH had no effect on the insulin content of islets [2]; low serum insulin in our study may be therefore due to changes in insulin secretion. Data show that low insulin increases GLUT2 mRNA expression in liver [77] ; in addition, liver GLUT2 expression in diabetic rats is higher, findings supporting the idea that hyperglycemia has a positive role in expression of GLUT2 [78]. To sum up, our findings showed that thyroid hormone deficiency during fetal life impairs glucose sensing apparatus in pancreatic islets and liver of offspring rats during adulthood, changes which may all be involved in impaired insulin sensitivity observed in our study.…”
Section: Discussionsupporting
confidence: 76%
“…We think that the increased expression of such factors in an early stage explains the increased insulin biosynthesis and secretion in an early stage. In addition, the increased expression of GLUT2 as well as glucokinase could explain the augmentation of glucose-stimulated insulin secretion in an early stage (Bae et al, 2010;Hay and Docherty, 2006;Waeber et al, 1996). Previous studies have suggested that the GLP-1 receptor expressions in pancreatic islets are decreased under hyperglycemia state (Kaneto and Matsuoka, 2013;Xu et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with this hypothesis, pre-treatment with the protein synthesis inhibitor, cycloheximide, abolished insulin induction of Gck (Figure S1L). Among transcription factors known to regulate Gck (Bae et al, 2010; Massa et al, 2011) (Figure S2A), Foxo1 , Foxo3 and Hnf4α mRNA showed a time-dependent increase after treatment with cAMP/dex (Figure S2B, C, and E), whereas Pparγ and Hnf6 expression decreased (Figure S2G and I), and Foxo4 , Hif1a and Srebf1 expression did not change (Figure S2D, F and H). The increase in Foxo1 and Hnf4α mRNA was due to dex (Figure S2J–L), and was associated with increased FOXO1 protein after 4h-treatment (Figure S2M–N).…”
Section: Resultsmentioning
confidence: 99%